Erasmus Mundus Masters Graduated Students' Follow-up: Formative and complementary itineraries and job prostpect - Manuel Fernández Cruz; José Gijón Puerta (Universidad de Granada, 2009)
In 2004 the EU began the challenging Erasmus Mundus Programme which consists of selecting high quality professional interuniversity and international master students in Europe. Sixteen of those masters already count with graduated students.Even though this is a well-known and appealing programme for non-European students European youth are not very familiar with it yet. An aim of the University should be the possibility to offer to their students the best option to achieve a successful professional insertion.Just as this moment we can deal with the study in depth of several aspects of these Masters, such as graduated professional insertion degree, quality of that insertion and guidance elements of Masters, and finally, the Universities that offer them.In order to develop a research for analyzing 54 Masters Erasmus Mundus, including 26 involved Universities and the present total amount of 160 graduated students, different sorts of instruments will be used.The research will use a comprehensive, illustrative, exploratory and descriptive methodology.